Potencial recombinogênico e citotóxico de um complexo metálico ternário de cobre associado a β–Dicetona e 1,10 Fenantrolina (CuBTAPhenClO4) - Lima, Paula Marynella Alves Pereira (2019)
Cancer is the second leading cause of death woroldwide, and breast is the most common in brazilian women, after non-melanoma skin. Chemotherapy is widely used for treatment of this disease, however, responsible for debilitating side effects. Therefore, it is necessary to search for more selective, less toxic drugs, and effective to combat tumor resistance. The present study aimed to evaluate the mutagenic / recombinogenic potential of the copper ternary metal complex associated with β-diketone and 1,10-phenanthroline (CBP-01), and its cytotoxicity in mammalian lineages, compared to routinely used compounds. The concentrations of the compound for in vivo mutagenicity / recombinogenicity test were established by the toxicity curve in D. melanogaster. The Somatic Recombination and Mutation Test - SMART was performed to evaluate the mutagenic and / or recombinogenic effect of CBP-01 (0.03mM, 0.06mM, 0,12mM and 0.25mM), Carboplatin (0.5mM) and Cisplatin (0.025mM). Subsequently, the MTT (bromide-3- (4,5-dimethylthiazol-2-yl) -2,5-diphenyltetrazolium) assays were conducted in order to verify the cytotoxicity of CBP-01, Carboplatin, Cisplatin and Doxorubicin, in diferents concentrations (1µM, 5µM, 10µM, 12.5µM, 25µM e 50µM), to breast cancer lineages T-47D (ductal carcinoma), MCF7 (luminal carcinoma) e MDA-MB-231 (triple-negative metastatic) and non-tumoral lineage MCF 10A. The lethal dose (LD) of CBP-01 in D. melanogaster was defined (0.4mM) and through the SMART test the recombinogenic potential of CBP-01 was only observed at the lowest concentration (0.03mM) and after its biotransformation, which suggests the generation of reactive substances capable of damaging the DNA. The other drugs induced high frequency of spots, confirming their recombinogenic / mutagenic potential. The results found by the MTT assay showed the selectivity of CBP-01, which was cytotoxic to tumor cell lines, especially against triple-negative cells, MDA-MB-231 (IC50 2.05 after 72 hours of treatment and selectivity index of 3.10) when compared to the other chemotherapeutic agents. CBP-01 is potentially promising for CM treatment, however, additional studies are needed to understand the molecular events mediated by their treatment, so that new therapeutic designs for CM will may be established.